ANULASI PERKAWINAN DALAM MOTU PROPRIO MITIS IUDEX DOMINUS IESUS DARI PAUS FRANSISKUS DAN RELEVANSINYA BAGI PERKAWINAN KATOLIK - Darmanto, Ignasius Anang Setia; Dewa, Febri Putra (Pastoralia Jurnal Penelitian Dosen, 2021)
The focus of this article is to explore the understanding of Catholic marriage annulation and the novelty carried out by Pope Francis through the Apostolic Letter Motu Proprio Mitis Iudex Dominus Iesus. This research was born after observing the divorce phenomenon that occurred in Indonesian society. The aim of this research is to explain the concept of annulation to Catholics and explain the purpose of Pope Francis in issuing the Apostolic Letter Motu Proprio Mitis Iudex Dominus Iesus which has an impact on the pastoral care of Catholic marriages. The research methodology used is qualitative with analytical descriptive writing methods. Qualitative research uses phenomenological and literature analysis. Data analysis was carried out to explain the meaning of annulation for Catholic marriages. The presence of the Apostolic Letter Motu Proprio Mitis Iudex Dominus Iesus brought reform to the annulation process. This has a direct impact on Catholic marital life today. The results of the analysis show that Catholic marriages do not recognize the term divorce because the Church values marriage as one and indissoluble. In the Apostolic Letter Motu Proprio Mitis Iudex Dominus Iesus, Pope Francis brought novelty by appointing   Bishops as judges themselves so that they could carry out a shorter annulation process while still paying attention to juridical requirements. It is this reform in the annulation that shows the role of the Church as a merciful image of God. The Church tries to embrace every congregation so that they do not feel alone in facing the marital problems they face. The Bishop's presence is increasingly real for God's people because the Bishop is the shepherd who feeds His sheep.